Is Adolescent Fertility High in Maluku Province? Indonesian Demographic and Health Survey (IDHS) Data Analysis in 2017 - Fandro Armando Tasijawa; Jino Tehusalawany; Vernando Yanry Lameky; Alisye Siahaya; Indah Benita Tiwery (Universitas Aisyah Pringsewu, 2021)
Adolescent fertility becomes an important issue for it gives an impact on education, employment, economic status, gender inequality, and poor health or death. The evidence was based on research to improve adolescent sexual and reproductive health. However, the matter of adolescent fertility was not well-known in Maluku Province. The importance of this problem to be investigated is related to what factors cause the high incidence of adolescent fertility in Maluku Province. The method used in this study was the quantitative approach of 2017 IDHS secondary data analysis which has received approval from the ICF Institutional Review Board. The population of this study were all female adolescents aged 15-19 years old in Maluku with a total sample of 371 respondents. The data analysis in this study consisted of univariate, bivariate and multivariate analysis. The results showed that the proportion of adolescent fertility in Maluku Province was 9,7%. It was found statistically that the variables of age, education, area of residence, marital status, contraceptive use and economic status had a significant relationship with adolescent fertility (p-value less than 0,05). This study also showed that the variable of age became the most dominant variable affecting the incidence of adolescent fertility.Abstrak: Fertilitas remaja menjadi isu penting karena berdampak pada pendidikan, pekerjaan, status ekonomi, ketidaksetaraan gender, dan kesehatan yang buruk atau kematian. Evidence based melalui penelitian untuk meningkatkan kesehatan seksual dan reproduksi remaja perlu ditingkatkan. Namun, masih terbatas yang diketahui tentang fertilitas remaja di Provinsi Maluku. Pentingnya permasalahan ini untuk diteliti terkait faktor-faktor apa saja yang menyebabkan tingginya kejadian fertilitas remaja di Provinsi Maluku. Metode pada penelitian ini menggunakan pendekatan kuantitatif analisis data sekunder SDKI tahun 2017 yang telah mendapat persetujuan dari ICF Institutional Review Board. Populasi penelitian ini adalah seluruh remaja wanita berusia 15-19 tahun di Maluku dengan total sampel 371 responden. Analisis data dalam penelitian ini terdiri dari analisis univariat, bivariat dan multivariat. Hasil penelitian menunjukkan proporsi fertilitas remaja di Provinsi Maluku sebesar 9,7%. Ditemukan secara statistik variabel umur, pendidikan, daerah tempat tinggal, status pernikahan, penggunaan kontrasepsi dan status ekonomi memiliki hubungan yang signifikan dengan fertilitas remaja (p-value kurang dari 0.05). Penelitian ini juga menunjukkan variabel umur menjadi variabel yang paling dominan mempengaruhi kejadian fertilitas remaja.